Prototype of Synchronous Double Brushless Direct Current Motor - Wahyu S. J. Saputra; Eva Yulia P; Ni Ketut Sari (Nusantara Science and Technology Proceedings)
Energy is one of the main needs in the current era. According to the law of conservation of energy, that energy can neither be created nor destroy, but energy can be change from one form to another. Energy can classify into two forms: the silent energy called the potential energy, and the moving energy called kinetic energy. The potential energy usually stored in raw energy sources are petroleum, coal, or still air. Kinetic energy usually stored in a negative energy source is wind or running water. Electricity is one form of energy that is widely used for various purposes a day. A lot of energy that turns into a form of electrical energy, one of which is petroleum. To simulate electrical goods by using electric energy more effectively. This paper a series of Double Brushless Direct Current Motor (BLDC) was create, to produce more effective motion energy in the utilization of electrical source. The prototype of this paper uses two equal BLDCs motor, one motor used as an AC generator to provide feedback from the resulting results. It expected that this prototype can be used as a tool of motion with effective electrical energy.